Wuelkerella toncekensis n. gen., n. sp. (Diptera: Chironomidae: Tanypodinae) from Argentina - Suárez, Diego A. Añón; Sublette, James E. (Zootaxa, 2012)
A new chironomid genus Wuelkerella is described. Pupae collected from the ultraoligotrophic Lakes Tonĉek and Jujuy, inRío Negro Province, Argentina were individually reared to adults. Pupa and adult male and female of Wuelkerella toncekensis sp. n. show intermediate features of Alotanypus Roback, Brundiniella Roback and Radotanypus Fittkau et Murray.